Definitive surgical closure of enterocutaneous fistula: outcome and factors predictive of increased postoperative morbidity. (March 2014) - Ravindran, P.; Ansari, N.; Young, C. J.; Solomon, M. J.
Abstract Aim Enterocutaneous fistula (ECF) presents a complex management problem with significant mortality and morbidity. The aim of this study was to assess the outcome of patients undergoing surgical cure for ECF and to predict factors that might relate to increased postoperative morbidity. Method Medical records of all patients who underwent definitive surgery for cure of an ECF within our colorectal surgery unit between 2000 and 2010 were reviewed. Results Forty‐one patients (18 male) were identified, in whom 44 definitive procedures were performed. The median age was 54 (17–81) years. The median postoperative length of stay in hospital was 14 (2–213) days. Half (50%) of the ECFs occurred as a postoperative complication followed by spontaneous fistulation in Crohn's disease (36%). The interval to definitive surgery was influenced by the aetiology of the fistula. The median time to surgery after formation of postoperative fistula was 240 days (7.9 months). There was no 30‐day postoperative mortality. There were two (4.5%) recurrences at 3 months. Thirty‐eight (86%) patients suffered postoperative morbidity as defined by the Clavien–Dindo classification. High‐grade morbidity occurred in 32% of patients. On univariate analysis, factors identified as being significantly associated with high‐grade morbidity included a fistula output of > 500 ml/day (P = 0.004) in patients with postoperative ECF, malnutrition at presentation (P = 0.04) and a serum albumin value of < 30 g/l (P = 0.02) in patients with spontaneous ECF due to Crohn's disease. Conclusion The majority of persistent complex ECFs can be cured surgically with low mortality and recurrence in a multidisciplinary setting. Postoperative morbidity, however, remains a significant burden.